Confirmations on gene introgression events and hybridity for BLB resistance and yield in rice - Ashan, Muh Aswad; Reflinur; Ardie, Sintho Wahyuning (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
A superior variety of rice with high yield and resistance to diseases is expected to meet the increasing demand for this one of the most important carbohydrate sources worldwide. Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the major biotic stresses limiting rice production. Combining BLB resistance and high-yield traits is possible through gene pyramiding. Introgression of targeted traits in the parental genotypes and hybridity confirmation in the F1 generation are important initial steps in gene pyramiding. This study aimed to confirm the presence of targeted genes in parent genotypes using specific molecular markers and to confirm the hybridity of F1 plants generated from three crosses combinations of Inpari 32 (as the female parent) and three Code-qTSN4 lines (as the male parents) using SSR markers. This study successfully confirmed the introgression of BLB-resistance genes in Inpari 32 (Xa4, Xa7, and Xa21) and in Code-qTSN4 (Xa4, Xa7). The introgression of yield-related QTL, qTSN4, was confirmed in the three Code-qTSN4 lines (A10-1, B12-2, and A16-5) by RM17483 marker. Five SSR markers (RM5, RM55, RM105, RM223, and RM561) successfully confirmed the hybridity of F1 derived from Inpari 32xA10-1 (five individuals), Inpari 32xB12-2 (one individual), Inpari 32xA16-5 (two individuals). These confirmed hybrids can be further evaluated in the F2 generation. Keywords: Gene pyramiding; molecular marker; SSR; qTSN4; Xoo.